2018
DOI: 10.1177/1687814018792316
|View full text |Cite
|
Sign up to set email alerts
|

Influence of fabric pretreatment on adhesion of three-dimensional printed material on textile substrates

Abstract: Adding three-dimensional printed objects on existing surfaces enables creation of multi-material objects with tailored mechanical properties. Especially, the tensile strength of a textile fabric is advantageous in comparison with threedimensional printed polymeric parts, while the latter can increase the stiffness of the composite. The adhesion forces between both material partners, however, are crucial for the reliability of the multi-material object. While several printing and material properties have been s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
78
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 56 publications
(81 citation statements)
references
References 18 publications
3
78
0
Order By: Relevance
“…Generally, more hydrophilic textile fabrics showed better adhesive properties [13]. A more detailed study of the infl uence of diverse chemical pre-treatments was performed recently, verifying the idea of hydrophilic properties being supportive of increased adhesion for several treatments, while a few outliers indicated that additional eff ects have to be taken into account [5]. A completely diff erent approach which has not yet been reported in the scientifi c literature is coating textile fabrics with a polymer solution prior to the 3D printing process.…”
Section: Increasing Adhesion Of 3d Printing On Textile Fabrics By Polmentioning
confidence: 95%
See 2 more Smart Citations
“…Generally, more hydrophilic textile fabrics showed better adhesive properties [13]. A more detailed study of the infl uence of diverse chemical pre-treatments was performed recently, verifying the idea of hydrophilic properties being supportive of increased adhesion for several treatments, while a few outliers indicated that additional eff ects have to be taken into account [5]. A completely diff erent approach which has not yet been reported in the scientifi c literature is coating textile fabrics with a polymer solution prior to the 3D printing process.…”
Section: Increasing Adhesion Of 3d Printing On Textile Fabrics By Polmentioning
confidence: 95%
“…[4]. However, most of these materials and the objects printed from them have insuffi cient mechanical properties for several applications [5,6]. In addition, the printing process is still relatively slow, as compared to die casting.…”
Section: Increasing Adhesion Of 3d Printing On Textile Fabrics By Polmentioning
confidence: 99%
See 1 more Smart Citation
“…The intensive development of manufacturing processes implies the possibility of their application in a lot of industry branches, e.g. in the aircraft industry, in the automotive industry, construction of components which work under constant loads [6][7][8] and in textile production [9]. Particularly important due to the efficiency of the manufacturing process is the application of additive technology to build foundry patterns, allowing immediate fabrication of the "first cast sample" [10][11][12].…”
Section: Introductionmentioning
confidence: 99%
“…3D printing on textile surfaces has been investigated allowing creating new multicomponent textiles and new optical properties [5,6]. Here, the adhesion between both materials still remains challenging and has led to further studies to enhance the bonding properties between two diff erent materials [7] due to fabric pre-treatment [8,9]. Furthermore, a study where fi brous materials were embedded in the printing process served as an input for this research [10].…”
mentioning
confidence: 99%